A Metapopulation Model Of Granuloma Formation In The Lung During Infection With Mycobacterium Tuberculosis - Suman Ganguli; David Gammack; Denise E. Kirschner (Mathematical Biosciences and Engineering)
The immune response to Mycobacterium tuberculosis infection (Mtb) is the formation of unique lesions, called granulomas. How well these granulomas form and function is a key issue that might explain why individuals experience different disease outcomes. The spatial structures of these granulomas are not well understood. In this paper, we use a metapopulation framework to develop a spatio-temporal model of the immune response to Mtb. Using this model, we are able to investigate the spatial organization of the immune response in the lungs to Mtb. We identify both host and pathogen factors that contribute to successful infection control. Additionally, we identify specific spatial interactions and mechanisms important for successful granuloma formation. These results can be further studied in the experimental setting.